HEAVY METAL CONTENTS IN MARINE SEDIMENTS AND SEAWATER AT TOTOK BAY AREA, NORTH SULAWESI - Delyuzar Ilahude (Marine Geological Institute of Indonesia, 2010)
The study area is located in north-eastern part of Tomini Bay, approximately 80 km south of Manado city, North Sulawesi. This area is closed to submarine tailing disposal system in Buyat Bay. Five marine sediment samples and four water samples from seawater and dig wells have been used for heavy metals (Hg, As, CN) analyses by using Atomic Absorption Spectrometry (AAS). This study is a part of research conducted by Marine Geological Institute of Indonesia on morphological changes of seabed in the Totok Bay. The result shows that concentration of mercury (Hg) in water samples taken from Ratatotok estuary is higher than standards stipulated Government Regulation (Peraturan Pemerintah/PP) No. 82/2001. Meanwhile, concentration of arsenic (As) is almost reaching its standard threshold, and conversely cyanide (CN) concentration is low. This value of mercury (Hg) concentration taken from Ratatotok estuary is much higher than water samples from of Buyat Bay estuary. Significant concentration of mercury (Hg) analysed from those particular sampling sites indicated high mercury contamination. Therefore, further examination on ground water of dig wells is necessary, especially for mercury analysis (Hg). Furthermore, comparing the formerly obtained data of mercury concentration in the sediment, this particular study concludes that the sediments in the Totok Bay had contaminated by mercury from gold-processing of illegal mining. Keywords: pollution, heavy metal, marine sediment, seawater, Totok Bay Daerah penelitian terletak di bagian timur laut Teluk Tomini, sekitar 80 km selatan kota Manado, Sulawesi Utara. Lokasi ini berdekatan dengan tempat pembuangan limbah tambang bawah laut di Teluk Buyat. Lima contoh sedimen laut, lima buah contoh air dari laut dan sumur telah digunakan untuk analisa logam berat (Hg, As, dan CN) menggunakan metode Atomic Absorption Spectrometry AAS. Studi ini merupakan bagian dari penelitian yang dilakukan oleh Marine Geological Institute of Indonesia tentang perubahan morfologi dasar laut di Teluk Totok. Hasil penelitian menunjukkan bahwa kandungan merkuri dalam contoh air yang diambil dari sekitar muara sungai Ratatotok lebih tinggi dari standar Peraturan Pemerintah/PP No. 82/2001. Sementara itu, konsentrasi arsen (As) hampir mencapai ambang batas standar dan konsentrasi sianida (CN) jauh lebih rendah dari standar ambang batas. Nilai kandungan merkuri di estuari Ratatotok lebih tinggi dibandingkan dengan contoh air yang terukur dari muara sungai di Teluk Buyat. Kandungan merkuri yang tinggi ini menunjukkan adanya indikasi pencemaran logam berat, dan oleh karena itu air di sumur-sumur penduduk perlu dilakukan penelitian lebih lanjut, khususnya untuk analisa merkuri. Selain itu, berdasarkan perbandingan kandungan merkuri dalam sedimen pada penelitian sebelumnya, dapat disimpulkan bahwa Teluk Totok telah mengalami kontaminasi merkuri dari penambangan emas ilegal. Kata kunci: polusi, logam berat, sedimen laut, air laut, Teluk Totok